THE IMPACT OF RISKS ON THE ECONOMIC SECURITY OF AIRLINES - Miziuk, Valentin; Miziuk, Svitlana (Proceedings of National Aviation University, 2016)
The paper considers the efficiency of measures to ensure the economic security of airlines. These measures are aimed at mitigating the risks related to committing acts of unlawful interference with civil aviation.